Analisis Strength, Weakness, Opportunity, and Threats Pembinaan Prestasi Tim Sepakbola Persepam Pamekasan - M. Hasan Basri; Achmad Widodo (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Sport is a physical activity that is needed by everyone in order to meet health and physical needs that are carried out systematically. Football is a sport that has the highest number of enthusiasts in the world from various circles. Achievements can be achieved through internal factors including athletes, coaches, administrators and external factors, including parental support. This research was motivated because there has been no research on Persepam Achievement Development based on SWOT analysis. The research was conducted to present the results of the analysis related to Persepam Pamekasan achievement development in order to improve the quality of the club, maximize existing support and minimize deficiencies and sources of threats that can hinder the Persepam Pamekasan achievement development program. This research is a qualitative descriptive study with a research target of 3 informants, namely administrators, coaches, and athletes. Data was obtained through interviews and documentation. This research produced several findings, including: (1) The most prominent strengths include: having quality coaches and potential athletes, and having effective and efficient governance. (2) The most influential weaknesses include minimal financial needs and inadequate facilities and infrastructure. (3) The most important opportunities include having many sources of support, such as athlete families, community enthusiasm and support from supporters, and developments that can be maximized. (4) The most feared threats include: not having a sponsor yet and the rapid development of other clubs. Alternative strategies that can be applied include: (1) immediately submitting a proposal to the company, (2) managing expenses and utilizing developments as best as possible, (3) optimizing available facilities, (4) increasing player potential, and (5) maintaining communication.